Investigation of power supply parameter effect on performance of vibrator meter with magnetic actuator - Tatyana I. Тupolskikh; Natalya V. Gucheva (Advanced Engineering Research, 2016)
The work objective is to study dosing accuracy changes of the vibration measurer with an electromagnetic drive powered by the industrial network. The previously obtained dependences of the vibration measurer performance on the vibration frequency, amplitude and direction of the magnetic actuator, and on the properties of the dispensed material are used. These relationships are obtained at the pilot plant with the stabilized power settings. It is found that the supply from the vibration agitator of the industrial network significantly (up to 5%) affects the vibrator meter performance deviation from the given one that may become unacceptable when dispensing the ingredients requiring higher accuracy. To eliminate uncontrolled deviations of the dispenser performance from the stochastic variations of voltage and frequency, a voltage- and frequency-stabilized supply of the vibration activator electromagnet should be used.